2022
DOI: 10.2147/jir.s341680
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Attenuates Alcohol-Induced Liver Injury and Inflammation via Blocking TLR4/MyD88/NF-κB Signaling Pathway

Abstract: Background: Alcoholic liver disease (ALD) is liver damage caused by long-term drinking. Inflammation plays a central role in the progression of ALD. CD73 is a ubiquitously expressed glycosylphosphatidylinositol-anchored glycoprotein that is a key enzyme that converts ATP into adenosine. Evidence has shown that CD73 plays an important role in many diseases, but the role and mechanism of CD73 in alcohol-induced liver injury and inflammation is still unclear. Methods: The alcohol-induced liver injury and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 48 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…The results showed that the expression of CD39 and CD73 increased in the EtOH-fed+CCl 4 group from the second week. Interestingly, inhibition of CD39 or CD73 aggravated inflammation 37 , 38 . Based on the previous experimental results, we believe that the increase of CD39 and CD73 in early-fibrotic-stage was a body's self-protection to liver inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the expression of CD39 and CD73 increased in the EtOH-fed+CCl 4 group from the second week. Interestingly, inhibition of CD39 or CD73 aggravated inflammation 37 , 38 . Based on the previous experimental results, we believe that the increase of CD39 and CD73 in early-fibrotic-stage was a body's self-protection to liver inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…As a hydrolytic product of CD73, adenosine can perform cell protective and immunosuppressive functions through P1 receptors, thus terminating liver inflammation and promoting liver regeneration. In addition, CD73 can block the TLR4/MyD88/NF-κB signaling pathway ( 52 ), reduce the secretion of IL-6 and IL-1β, and delay the inflammatory process. In liver biopsies of NAFLD patients, CD73mRNA levels were significantly reduced ( 9 ), so CD73 knockout mice rarely developed fatty liver disease, or even progressed to steatohepatitis ( 13 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…After CD73 deletion, adenosine production is reduced, resulting in the suppression of HSC activation and proliferation mediated by p2 receptor and decreased collagen expression, inhibiting the production of liver fibrosis. Meanwhile, inhibition of CD73 can promote HSC apoptosis and alleviate alcohol-induced liver fibrosis ( 52 ). Similarly, A2A adenosine receptor deficient mice were also protected from the effects of liver fibrosis by blocking the adenosine pathway ( 60 ).…”
Section: Manuscript Formattingmentioning
confidence: 99%
“…Metabolites and signalling molecules produced by gut microbes can impact nerve signalling and brain functions through several mechanisms such as the transportation of neurotransmitters or via circulation within the bloodstream (Wekerle, 2018 ). The equilibrium of gut microbiota can be disrupted by alcohol consumption, inducing dysbiosis (Brüssow, 2020 ) and a consequential overgrowth of deleterious microorganisms (Liu, Guo, et al, 2022 ; Liu, Vigorito, et al, 2022 ; Liu, Wu, et al, 2022 ). The toxins these microorganisms release can translocate across the intestinal mucosa, enter the bloodstream and breach the blood–brain barrier (Logsdon et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%